Stress and tinnitus—from bedside to bench and back - Mazurek, Birgit; Haupt, Heidemarie; Olze, Heidi; Szczepek, Agnieszka J. (Frontiers in Systems Neuroscience, 2012)
The aim of this review is to focus the attention of clinicians and basic researchers on the association between emotional stress and tinnitus. Although tinnitus is an auditory symptom, its onset and progression often associates with emotional strain. Recent epidemiological studies have provided evidence for a direct relationship between the emotional status of subjects and tinnitus. In addition, studies of function, morphology, and gene and protein expression in the auditory system of animals exposed to stress support the notion that the emotional status can influence the auditory system. The data provided by clinical and basic research with use of animal stress models offers valuable clues for an improvement in diagnosis and more effective treatment of tinnitus.